Adverse Childhood Experiences and Diabetes: Testing Violence and Distress Mediational Pathways in Family Medicine Patients - Strenth, Chance R. (Journal of interpersonal violence, 2022)
Type 2 diabetes mellitus (diabetes) is increasing in frequency and creating a significant burden on the United States healthcare system. Adverse childhood experiences (ACE) and interpersonal violence (IV) have been shown to have detrimental effects on mental and physical health. How ACE can influence IV as an adult and how this can influence the management of diabetes is not known. The purpose of the current study is to understand the relationship between violence and social determinants of health (SDoH), and its effect on patients with type 2 diabetes mellitus. A practiced-based research network (PBRN) of family medicine residency programs was utilized to collect cross-sectional data from seven family medicine residency program primary care clinics. In total, 581 participants with type 2 diabetes were recruited. A serial/parallel mediation model were analyzed. The majority of participants (58.3%) had a Hemoglobin A1c (HbA1c) that was not controlled. ACE was associated with an increase in Hurt-Insult-Threaten-Scream (HITS) scores, which in turn was positively associated with an increase in emotional burden, and finally, emotional burden decreased the likelihood that one?s HbA1c was controlled (Effect = ?.054, SE = .026 CI [?.115, ?.013]). This indirect pathway remained significant even after controlling for several SDoH and gender. The impact of ACE persists into adulthood by altering behaviors that make adults more prone to experiencing family/partner violence. This in turn makes one more emotionally distressed about their diabetes, which influences how people manage their chronic condition. Family physicians should consider screening for both ACE and family/partner violence in those patients with poorly controlled diabetes.